Assessment of wheeled mobility devices provided to a commercially insured population in 2017. Issue 3 (4th May 2022) - Sprigle, Stephen; Chen, Jie; Hughes, Danny
ABSTRACT: In the United States, wheeled mobility devices (WMD) are classified as durable medical equipment (DME). Consistent with the definition of DME, wheeled mobility devices are typically covered by health insurance when deemed medically necessary. Despite the number of persons using wheelchairs, little knowledge is available about the types of wheelchairs provided, user's specific diagnoses and the costs associated with WMD provision. The objective of this analysis was to define the number and types of wheelchairs and associated seating and mobility (S&M) accessories provided in the calendar year 2017. The analysis focused on user demographics, categories of WMDs and associated S&M equipment as well as cost accounting according to the type of insurance and contributions by beneficiaries. Analysis of over 81, 000 wheelchair acquisitions found that manual wheelchairs accounted for nearly 90% with standard manual wheelchairs accounting for 86% of all wheelchairs provided. Wheelchair recipients tended to be older with the majority being female. Based upon ICD-10 diagnostic categories over 50% of captured ICD-10 codes came from three classifications, musculoskeletal (M), circulatory (I) and a general category of not otherwise classified disorders (R). Costs associated with seating and mobility equipment were fairly large, exceeding $79 million over a single calendar year.